Polycystic Ovary Syndrome in Adolescence: Challenges in Diagnosis and Management - Manique, Mariana Enxuto Santos; Ferreira, Ana Margarida Antunes Póvoa (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Diagnosing polycystic ovary syndrome (PCOS) during adolescence is challenging since normal pubertal development overlap typical features of this syndrome. The authors aim to summarize the existing evidence concerning PCOS in adolescence, particularly its diagnostic criteria and therapeutic options. A search throughout medical databases such as PubMed and MedScape was performed. Diagnostic criteria include irregular menstrual cycles according to time postmenarche and evidence of clinical hyperandrogenism and/or biochemical hyperandrogenism, provided other causes have been excluded. Polycystic ovarian morphology ought not to be used as a diagnostic criterion. Treatment should target manifestations and/or comorbidities, even in the absence of a definite diagnosis. Lifestyle interventions are the first-line treatment. Combined oral contraceptives, metformin or antiandrogens may also be considered as adjuvants. Screening for PCOS in adolescence is crucial as it allows an early intervention on the symptoms and comorbidities presented leading to better long-term reproductive and metabolic outcomes.
Keywords: polycystic ovary syndrome; adolescence; diagnosis; management